REVOLUTION IN PPI OR REVOLT? A MEETING OF MINDS OR A CLASH OF OPINIONS. Issue 6 (19th May 2015) - Irving, Andy; Broadway-Parkinson, Andrea; Marsh, Maggie; Fall, Dan
Abstract : Background: The PhOEBE (Pre-Hospital Outcomes for Evidence Based Evaluation) research programme aims to develop new ways of measuring how well ambulance services meet the needs of the patients who call them and the quality of the care they provide. Measuring how services are performing is important as it allows us to monitor if standards are being maintained, assess what works well and identify problems early so improvements can be made. The first stages of our programme have focused on identifying the range of possible measures and from these narrowing it down to a small number that we will then develop in more detail. Methods: A Delphi survey was planned for PPI and 'experts' to score how useful they thought each potential measure was. At the outset of the survey preparation, the PhOEBE PPI group highlighted concerns regarding the accessibility of the method for a lay audience. Alternative means of involving patient and public views were considered. The PPI reference group co-designed a more interactive and accessible consensus event open to a wider PPI audience in order to consider those measures favoured by the Delphi expert panel. The event included presentations, small group discussions facilitated by the PhOEBE PPI ref group and electronic voting. Results: Of the thirty one measures presented nine were voted as most relevant and important from a lay perspective. Conclusion: This event not only provided the project with valuable information about which of our potential measures are considered important but also demonstrated that a PPI led initiative can enhance a lay audience's understanding of ambulance service performance issues. Despite some challenges in communication the event proved the PPI ref group as valued research collaborators. We continue to develop a more proactive PPI-led model of involvement capable of meeting the needs of the PhOEBE programme.